Adolescents’ perceptions of covitality and academic performance: The moderating role of school climate - Stasinou, Vasiliki; Hatzichristou, Chryse; Lampropoulou, Aikaterini; Lianos, Panayiotis (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Children’s and adolescents’ psychosocial adjustment has been studied in relation to various factors at an individual and system level aiming at identifying the variables that contribute, as protective factors, to the promotion of their social and emotional health and covitality. This study examined the link between covitality, which describes the co-occurrence of basic positive psychology constructs, and the perceptions of Greek junior high school students regarding school climate. The sample consisted of 745 adolescent students (mean age 14.4 years) from randomly selected junior high schools in the broader area of Athens, Greece. The Social-Emotional Health Survey–Secondary (SEHS-S), CHKS Supplemental School Climate Module, students’ academic performance, and a questionnaire of socio-demographic data were used. Findings indicated the existence of statistically significant relations between adolescents’ perceptions of social and emotional health and school climate. Furthermore, significant differences were found in relation to school performance and parents’ unemployment. Conditional process analyses showed that several school climate dimensions (i.e. Support for learning, Discipline, and Order, Peer relations, Social-emotional support, Environment) moderated the direct effect of school performance on covitality. Furthermore, father’s unemployment added to the prediction of covitality by school climate. The results provide a better understanding of adolescents’ development and highlight the critical role of positive school climate on students’ psychosocial adjustment providing implications for developing effective interventions in school communities.